Factors associated with HPV vaccine acceptability and hesitancy among Black mothers with young daughters in the United States - Gray, Aaliyah; Fisher, Celia B. (Frontiers in Public Health, 2023)
Compared to other-race peers, Black women are disproportionately impacted by human papillomavirus [HPV] infection, related health outcomes, and cervical cancer mortality as a result of suboptimal HPV vaccine uptake during adolescence. Few studies have examined psychosocial determinants of HPV vaccine acceptability and hesitancy among Black parents. The current study integrated the health belief model and the theory of planned behavior to evaluate the extent to which psychosocial factors are associated with pediatric HPV vaccination intentions among this population. Black mothers (N = 402; age range = 25 to 69 years, M = 37.45, SD = 7.88) of daughters ages 9 to 15 years completed an online survey assessing HPV infection and vaccine beliefs and attitudes across four domains: Mother’s HPV Perceptions, Mother’s Vaccine Attitudes, Cues to Action, and Perceived Barriers to HPV Vaccination. Participants indicated their willingness to vaccinate their daughter on a 5-level ordinal scale (“I will definitely not have my daughter get the vaccine” to “I will definitely have my daughter get the vaccine”) which was dichotomously recoded for bivariate logistic regressions. Half of the sample (48%) intended to vaccinate their daughter. Number of daughters, mother’s HPV vaccine status, perceived HPV vaccine benefits, HPV vaccine safety concerns, pediatric HPV vaccine peer norms, and doctor recommendations emerged as independent factors of Black mothers’ intentions to vaccinate their daughters against HPV when controlling for all other factors. In addition to medical training to increase doctor recommendation of the HPV vaccine for Black girls, population-tailored public health messaging aimed at promoting HPV vaccine acceptance among Black mothers is urgently needed. This messaging should engage community support and emphasize the benefits of vaccination for adolescent Black girls while also addressing parental concerns regarding the safety of pediatric HPV vaccination.